Utilisation of Agricultural Activities as a New Strategy to Overcome Frailty Symptoms in Menopausal Women in Rural Areas - Fitria, Rahmi; Handayani, Eka Yuli; Wulandari, Sri; Aldriana, Nana (Universitas Airlangga, 2025)
Background: Menopause, typically occurring between the ages of 45 and 55, often brings physical and mental health challenges, with frailty being a significant concern. Frailty leads to decreased muscle strength, poor balance, and increased susceptibility to chronic diseases. Limited research focuses on nature-based interventions, such as agricultural activities, to reduce frailty symptoms in menopausal women, particularly in rural areas. Objective: This study aims to explore the effectiveness of agricultural activities in reducing frailty symptoms among menopausal women in the Rambah District and to assess their impact on physical health and mental well-being. Methods: An experimental design with a pre-test and post-test approach was used. Sixty menopausal women from Rambah District were divided randomly into an experimental group (agricultural program) and a control group. Frailty symptoms were assessed using the Fried Frailty Criteria, and mental health was measured with the Beck Depression Scale and Hamilton Anxiety Scale. Data analysis included normality tests, homogeneity tests, and independent samples t-tests. Results: The experimental group showed a significant improvement in frailty symptoms, with the average score increasing from 15.22 to 76.11.In contrast, the control group exhibited modest improvements. Statistical analysis confirmed the normality of the data and equal variances between groups. Conclusion: This study shows that agricultural activities are an effective and accessible intervention for reducing frailty symptoms in menopausal women, particularly in rural areas. It suggests that community-based programs using local resources, such as farming, can significantly improve both the physical and mental health of menopausal women, offering a sustainable solution for health promotion in rural communities.